Efficacy of bevacizumab in first-line treatment of metastatic colorectal cancer: A systematic review and meta-analysis. (January 2019) - Baraniskin, Alexander; Buchberger, Barbara; Pox, Christian; Graeven, Ulli; Holch, Julian W.; Schmiegel, Wolff; Heinemann, Volker
Abstract: Background: This systematic review and meta-analysis aims to evaluate the additive effect of bevacizumab when combined with first-line chemotherapy in metastatic colorectal cancer (mCRC). Methods: We searched EMBASE, MEDLINE, the Cochrane Library in April 2018. When possible, data were pooled to estimate summary effects. The present analysis evaluated treatment related efficacy based on progression-free survival (PFS) and overall survival (OS). The analysis was performed to define the overall effect and the effect observed in currently used chemotherapy regimens. Results: Seven randomised studies were included. In the analysis of the overall effect, PFS (hazard ratio [HR] 0.71, p < 0.00001) and OS (HR 0.85, p = 0.0008) clearly favoured bevacizumab plus chemotherapy versus chemotherapy alone. When the analysis was focused on currently used chemotherapy excluding 5-FU bolus regimens and including only infusional 5-FU plus irinotecan or oxaliplatin, the addition of bevacizumab prolonged PFS (HR 0.79, p < 0.0001) but not OS (HR 0.92, p = 0.18). However, addition of bevacizumab to fluoropyrimidine monotherapy lead to a significant prolongation of PFS (HR 0.57, p < 0.00001) and OS (HR 0.83, p = 0.03). Conclusion: The present meta-analysis demonstrates that the effect of bevacizumab on survival is not consistent throughout the included regimens. Considering only presently used regimens, a significant effect on PFS and OS was only observed when bevacizumab was added to fluoropyrimidine monotherapy. Highlights: The effect of bevacizumab on survival is not consistent throughout all chemotherapy regimens. The addition of bevacizumab to infusional 5-FU plus irinotecan or oxaliplatin prolonged PFS but not OS. A significant effect on PFS and OS was only observed when bevacizumab was added to fluoropyrimidine monotherapy.